I am totally lost on how to solve

g(x)=2x^2+3x-1 to find the y and x-intercepts.
This is what I have so far, but I don't know if I am on the right track. And if so what would be next?
g(x)=2x^2+3x-1
=2x^2+3x -1
=(2x^2+3+6) +3-1

1 answer

Get y-intercept when x=0
g(x) = y = 2(0)^2 + 3(0) - 1
(0,-1) ; y-intercept = -1

x-intercept: set function equal to 0
2x^2 + 3x - 1 = 0
After quadratic equation...
x-intercepts: x = -1.78, and x = 0.28

function to the 2nd power of x, so is a parabola opening upwards. Graphing the function verifies the answers.